Tendencias en el desempe\~no financiero de las empresas multinacionales y la estrategia de traslado de actividades en la búsqueda de competitividad: Una muestra del sector manufacturero en Puerto Rico - Doris Morales-Rodríguez (Atlantic Review of Economics, 2013)
– This paper present the trends in the financial performance and decisions making strategies about the closing and/or relocation of manufacturing industries based in Puerto Rico during the years 2005 to 2010. The paper point out a comparison in the financial performance between those companies that closed with those that relocated its business or closing for other reasons, such as terms of profitability indicators (net income, return on assets, return on equity, return on investment and Ebit margin) and liquidity (debt over assets, debt to equity and liquidity ratio). The sample was chosen through statistical reports manufacturers closing from the Workforce Development Administration of the Department of Labor and Human Resources of Puerto Rico. The financial data were obtained from the Compustat data base of Standard & Poor's. The paper conclude that the strategies for the relocation of activities was based taking in consideration to improve the competitiveness and financial performance, while the closing of operations could be aimed to improve the solvency and face up economics situations of these firms.
Keywords: 330; closing operations; relocation; financial performance; competitiveness; strategic decisions